Effect of Ecoenzyme Application for Cayenne Pepper Storage - Ratna Dewi Eskundari; Suwaji Handaru Wardoyo; Alya Febrina Azzahra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Cayenne pepper is one of vegetables that is consumed almost every day by every household. However, cayenne pepper is characterized by not being long-lasting, so efforts are needed to extend the shelf life of cayenne peppers. Ecoenzyme is known as a multipurpose solution that has antimicrobial properties, so it is thought that ecoenzyme can be used as a natural preservative, for example to extend the shelf life cayenne pepper. This research aims to determine the effectiveness of ecoenzyme solutions in extending the shelf life of cayenne pepper. The research was carried out using fruit-derived ecoenzyme solution and vegetable-derived ecoenzyme solution, with treatment without dilution, ecoenzyme solutions with a concentration of 75%, and ecoenzyme solutions with a concentration of 50%. The results of the research showed that at full concentration without dilution, fruit-derived or vegetables-derived ecoenzyme solution can extend the shelf life of cayenne pepper to 10 days. It is hoped that these results will be useful for post-harvest purposes of cayenne pepper, both on a household and larger scale.